APOE ε4 Allele Distribution and Association With Scores of Subjective Cognitive Decline Questionnaire 9 in a Large Chinese Memory Clinic Cohort - Hao, Lixiao; Jia, Jianguo; Xing, Yue; Han, Ying (Frontiers in Neuroscience, 2022)
Background: Previous reports on APOE ε4 allele distribution in different populations have been inconclusive. The Subjective Cognitive Decline Questionnaire 9 (SCD-Q9) was developed to identify those at risk of objective cognitive impairment [OCI, including mild cognitive impairment (MCI) and dementia groups), but its association with APOE ε4 and discriminatory powers for SCDwith subtle cognitive decline (SCDs) and OCI in memory clinics are unclear. Objectives: To investigate demographic distribution of APOE ε4, its association with SCD-Q9 scores, and its ability to discriminate SCDs and OCI groups from normal control (NC). Methods: 632 participants were recruited (NC=243, SCDs=298, OCI=91). APOE ε4 allele distribution and association with SCD-Q9 scores were calculated a the effects on cognitive impairment analyzed. Receiver operating characteristic (ROC) analysis was applied to identify discriminatory powers for NC, SCDs, and OCI. Results: Total APOE ε4 frequency was 13.1%. This did not vary by demography but was higher in patients with OCI. The SCD-Q9 scores were higher in APOE ε4 carriers than non-carriers in the OCI group. The area under the curve (AUC) for discriminating from NC using APOE ε4 were 0.587 and 0.575, using SCD-Q9 scores were 0.727 and 0.738 for SCDs and OCI groups, respectively. When we combined APOE ε4 and SCD-Q9 scores into the model, the AUC increased to 0.747 for discriminating OCI from NC. However, when OCI group was split into MCI and dementia groups, only total SCD-Q9 score was the independent affecting factor of MCI. Conclusions: This study demonstrated that the distribution of APOE ε4 alleles did not vary with different demographic characteristics in a large-scale cohort from a memory clinic. APOE ε4 alleles may be associated with scores of SCD-Q9 reflecting the degree of cognitive complaints but their additional contribution to SCD-Q9 scores is marginal in discriminating between NC, SCDs and OCI.